Implementasi Sosialisasi Basic Life Support Melalui Media Berbasis Qr Code untuk Meningkatkan Profesionalitas Perawat di Ruang IGD RSKGM Provinsi Sumatera Selatan - Indra Pratama; Sentot Imam Suprapto (Yayasan Inspirasi El Burhani, 2026)
Introduction: Basic Life Support (BLS) competency is essential for emergency nurses to ensure prompt and appropriate management of life-threatening conditions. A situational assessment conducted at the Emergency Department of the South Sumatra Provincial Dental Hospital revealed that BLS education was still delivered using conventional methods, limiting opportunities for continuous learning and competency retention. Therefore, an innovative digital learning approach utilizing QR Code technology was introduced to support sustainable professional development. Objective: The purpose of this community service was to improve the professionalism of emergency nurses through the implementation of QR Code-based Basic Life Support education. Method: This community service employed a participatory approach involving 11 emergency nurses. Problem identification was conducted using Fishbone analysis, followed by problem prioritization through the Urgency, Seriousness, and Growth (USG) method and strategic planning using SWOT analysis. The intervention consisted of health education, interactive discussions, demonstrations, and the implementation of QR Code-based learning media containing BLS modules, algorithms, standard operating procedures, instructional videos, and self-learning materials. Program effectiveness was evaluated using pre-test and post-test assessments, with data analyzed using the Paired Samples t-test. Result: The program successfully developed and implemented QR Code-based educational media that facilitated continuous and independent learning. The mean pre-test score increased from 8.00 ± 1.265 to 9.64 ± 0.809 after the intervention, with a mean improvement of 1.64 points. Statistical analysis demonstrated a significant difference between pre-test and post-test scores (t = -6.708; p < 0.001), indicating that the intervention effectively improved nurses' knowledge and preparedness in Basic Life Support. Conclusion: QR Code-based Basic Life Support education is an effective and innovative strategy for strengthening nurses' knowledge, supporting continuous professional development, and improving professionalism, emergency care quality, and patient safety.